Małżeństwo niesakramentalne chrześcijan - Janczewski, Zbigniew (Ius Matrimoniale, 2007)
We read on the canon 1055: a valid marriage contract cannot exist between baptised persons without its being by th at very fact a sacrament”. In the year 1563 Trident Synod announced the dogma about sacramentality o f marriage. Author of this publication analyses the documents o f Holy See details relative to question of the marriage not baptised persons and Christian person with not baptised person. The pope dissolves such valid contract on the Peters privilege - in favorem fidei. He can dissolves valid bu t only not sacramental contracts. Therefore - that marriage is not sacramental. He shows also regulations of canon law relate to make contract between catholic people and not baptised, and problems catholics - moslems marriages.